Endometrial adenocarcinoma in the oncology department of the Goyeneche Hospital in Arequipa - Juarez Hinojosa, Néstor (2015)
Endometrial adenocarcinoma ranks second in frequency among malignant neoplasms of the female genital tract, and that is the reason why we thought it convenient to report the incidence of this neoplasm in the Oncology Service Goyeneche Hospital in Arequipa. The uterus is the organ par excellence carcinogenic and which has the highest incidence of malignancy of women.